Early MRI predictors of disease-free survival in locally advanced rectal cancer from the GRECCAR 4 trial. Issue 11 (22nd August 2019) - Nougaret, S; Castan, F; Forges, H; Vargas, H A; Gallix, B; Gourgou, S; Rouanet, P; Rullier, E; Lelong, B; Maingon, P; Tuech, J-J; Pezet, D; et al.
Abstract: Background: Tailored neoadjuvant treatment of locally advanced rectal cancer (LARC) may improve outcomes. The aim of this study was to determine early MRI prognostic parameters with which to stratify neoadjuvant treatment in patients with LARC. Methods: All patients from a prospective, phase II, multicentre randomized study (GRECCAR4; NCT01333709) were included, and underwent rectal MRI before treatment, 4 weeks after induction chemotherapy and after completion of chemoradiotherapy (CRT). Tumour volumetry, MRI tumour regression grade (mrTRG), T and N categories, circumferential resection margin (CRM) status and extramural vascular invasion identified by MRI (mrEMVI) were evaluated. Results: A total of 133 randomized patients were analysed. Median follow-up was 41·4 (95 per cent c.i. 36·6 to 45·2) months. Thirty-one patients (23·3 per cent) developed tumour recurrence. In univariable analysis, mrEMVI at baseline was the only prognostic factor associated with poorer outcome ( P =  0·015). After induction chemotherapy, a larger tumour volume on MRI ( P =  0·019), tumour volume regression of 60 per cent or less ( P =  0·002), involvement of the CRM ( P =  0·037), mrEMVI ( P =  0·026) and a poor mrTRG ( P =  0·023) were associated with poor outcome. After completion of CRT, the absence of complete response on MRI ( P =  0·004), mrEMVI ( P =  0·038) and a poor mrTRG ( P =  0·005) were associated with shorter disease-free survival. A final multivariable model including all significant variables (baseline, after induction, after CRT) revealed that Eastern Cooperative Oncology Group performance status ( P =  0·011), sphincter involvement ( P =  0·009), mrEMVI at baseline ( P =  0·002) and early tumour volume regression of 60 per cent or less after induction ( P =  0·007) were associated with relapse. Conclusion: Baseline and early post-treatment MRI parameters are associated with prognosis in LARC. Future preoperative treatment should stratify treatment according to baseline mrEMVI status and early tumour volume regression. Graphical Abstract: Patients with locally advanced rectal cancer from the multicentre phase II randomized study GRECCAR 4 were included in the study, and underwent rectal MRI before and after induction chemoradiotherapy. Baseline and early post-treatment MRI parameters were associated with prognosis in locally advanced rectal cancer. Future preoperative therapy evaluation will need to stratify treatment according to baseline extramural vascular invasion status and early tumour volume regression. Tailored treatment possible